2020
DOI: 10.13031/aea.13969
|View full text |Cite
|
Sign up to set email alerts
|

Rainwater Harvesting with Solar and Gravity Powered Irrigation for High Tunnels

Abstract: HIGHLIGHTS Captured rainwater supplied nearly all the irrigation required for high tunnels in Tennessee. Solar pumping and/or gravity flow adequately supplied the pressure required for irrigation in high tunnels. Rainwater harvesting costs need to be reduced in order to be more com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Nearly 30% of the total irrigated land area in the U.S. is located in the eastern humid states, and the area continues to increase (USDA-NASS, 2018). Overall, eight journal articles for this ASABE Special Collection were related to agricultural irrigation in the humid region, with three articles specifically discussed in this section (Leib et al, 2020;Lena et al, 2020;Reinhart et al, 2020). The other five articles were discussed in the Technology and Innovation section (Chiu and Reba, 2020;Henry, et al, 2020;Lo et al, 2020), the Irrigation Systems section (Reba and Massey, 2020), and the Irrigation Management section (Zamora-Re et al, 2020).…”
Section: Irrigation In the Humid Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly 30% of the total irrigated land area in the U.S. is located in the eastern humid states, and the area continues to increase (USDA-NASS, 2018). Overall, eight journal articles for this ASABE Special Collection were related to agricultural irrigation in the humid region, with three articles specifically discussed in this section (Leib et al, 2020;Lena et al, 2020;Reinhart et al, 2020). The other five articles were discussed in the Technology and Innovation section (Chiu and Reba, 2020;Henry, et al, 2020;Lo et al, 2020), the Irrigation Systems section (Reba and Massey, 2020), and the Irrigation Management section (Zamora-Re et al, 2020).…”
Section: Irrigation In the Humid Regionmentioning
confidence: 99%
“…Rainwater harvesting (RWH) was sufficient to meet irrigation needs for high tunnels (i.e., simple greenhouse structures using plastic film) in Tennessee (Leib et al, 2020) in a comparison of three different RWH systems (gravity flow, solar transfer pumping, and solar battery-powered pumping). The authors concluded that the costs of the three tested RWH systems were not competitive with the cost of using alternative water sources.…”
Section: Irrigation In the Humid Regionmentioning
confidence: 99%